Challenges in Enforcing Copyright Law Amid the Rise of Illegal Movie Streaming in Indonesia - Dalva Aulia Apandi; Distya Rahma Fauziah; Euis Maesaroh; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid development of digital technology has transformed the distribution and consumption of cinematographic works through online streaming services, while simultaneously increasing the prevalence of illegal movie streaming activities. This study aims to examine the legal protection of cinematographic copyrights, identify the forms and driving factors of illegal movie streaming, and analyze the challenges of copyright law enforcement in Indonesia. The research employed a normative legal method using statutory and conceptual approaches through an extensive library-based review of legal instruments, academic literature, and relevant scholarly studies. The findings indicate that cinematographic works are protected under Indonesian Copyright Law through moral rights, economic rights, and related rights granted to creators and rights holders. Copyright infringements occur in various forms, including unauthorized streaming, illegal hosting, hyperlink distribution, camcording, re-encoding, and the circumvention of digital protection measures. Law enforcement efforts remain constrained by technological developments, cross-border jurisdictional issues, institutional coordination challenges, and limited public awareness of copyright protection. Strengthening copyright governance therefore requires an integrated approach involving regulatory reform, technological safeguards, interagency cooperation, and public education to enhance legal compliance in the digital era.